The Influence of Predict Observe Explain (POE) Learning Model on Student Learning Outcomes - Prabawati, Reni; W.H., Nugrahaningsih; Alimah, Siti (Journal of Biology Education, 2020)
This study aims to analyze the influence of Predict Observe Explain (POE) model on student’s learning outcomes. This research was conducted using Quasi Experimental design with Pretest-Posttest Control Group Design. Population of this research is all of XI grade students at MA Al Asror Semarang. The sample that were used are XI IPA 1 as control class and XI IPA 2 as experimental class taken by simple random sampling. The result showed that the learning outcomes experiment class are better than control class in term of cognitive, affective, and psychomotor aspects. The result of N-gain t-test shows there is significant difference of posttest-pretest value between experiment class and control class. The level of affective and psychomotor aspects of the experimental class is better than the control class. This is supported by the responses of teachers and students who respond well to learning with POE model applied. Based on the results of the study concluded that the learning of Predict Observe Explain (POE) model applied have a significant effect on students’s learning outcomes.